Chemical genetics approaches for selective intervention in epigenetics. (August 2016) - Runcie, Andrew C; Chan, Kwok-Ho; Zengerle, Michael; Ciulli, Alessio
Graphical abstract: In conventional chemical genetics, cell-active small-molecules directly block protein activity, altering phenotype. However these molecules may not be sufficiently selective or effective at modulating complex epigenetic pathways. By mutating the target protein, and creating a mutant-selective inhibitor, the bump-and-hole approach can provide single-target selectivity. PROTAC molecules direct their target to proteosomal degradation by recruiting an E3 ubiquitin ligase, resulting in more efficacious target downregulation. Highlights: Chemical genetics offers tools and opportunities to investigate epigenetic processes. Chemical probes targeting epigenetic proteins are increasingly being developed. Epigenetic targets pose distinct challenges to chemical genetics approaches. The 'bump-and-hole' approach allows for highly selective single-target inhibition. PROTACS can degrade target proteins to enhance efficacy and selectivity. Abstract : Chemical genetics is the use of biologically active small molecules (chemical probes) to investigate the functions of gene products, through the modulation of protein activity. Recent years have seen significant progress in the application of chemical genetics to study epigenetics, following the development of new chemical probes, a growing appreciation of the role of epigenetics in disease and a recognition of the need and utility of high-quality, cell-active chemical probes. In this review, we single out the bromodomain reader domains as a prime example of both the success, and challenges facing chemical genetics. The difficulty in generating single-target selectivity has long been a thorn in the side of chemical genetics, however, recent developments in advanced forms of chemical genetics promise to bypass this, and other, limitations. The 'bump-and-hole' approach has now been used to probe — for the first time — the BET bromodomain subfamily with single-target selectivity and may be applicable to other epigenetic domains. Meanwhile, PROTAC compounds have been shown to be significantly more efficacious than standard domain inhibitors, and have the potential to enhance target selectivity.